Empowering the Future: Exploring the Role of Youth Participation in Climate Change Mitigation and Adaptation (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study examines the impact of demographic factors, specifically education, age, occupation, and community support, on youth engagement in climate change mitigation and adaptation. Using a mixed-methods approach, data from 117 respondents were analyzed through ANOVA, correlation, and regression to assess climate awareness and perceived empowerment. Results indicate that higher education levels are significantly associated with climate literacy and proactive climate behaviors, while community support is essential in enhancing youth confidence in climate actions. A notable gap between awareness and empowerment highlights the need for targeted educational programs and supportive policies. This research suggests that integrating climate education at various educational levels and building community-based support networks can foster youth empowerment and sustainable climate leadership.